2007
DOI: 10.1088/0957-4484/18/10/105104
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver and gold nanoparticles by novel sundriedCinnamomum camphoraleaf

Abstract: The synthesis of nanocrystals is in the limelight in modern nanotechnology. Biosynthesis of nanoparticles by plant extracts is currently under exploitation. Not only could silver nanoparticles ranging from 55 to 80 nm in size be fabricated, but also triangular or spherical shaped gold nanoparticles could be easily modulated by reacting the novel sundried biomass of Cinnamomum camphora leaf with aqueous silver or gold precursors at ambient temperature. The marked difference of shape control between gold and sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
797
1
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,550 publications
(851 citation statements)
references
References 35 publications
45
797
1
8
Order By: Relevance
“…A comparison of our XRD spectrum with the standard confirmed that the silver particles formed in our experiments were in the form of nanocrystals, as evidenced by the peaks at 2 毴 values of 26.2 曘 , 27.9 曘 , and 32.3 曘 , corresponding to (125), (226), and (264), respectively, for silver. The X-ray diffraction results clearly show that the silver nanoparticles formed by the reduction of Ag + ions by the C. roseus leaf extract are crystalline in nature [26] . As mentioned in the method section, the silver nanoparticles once formed were repeatedly centrifuged and redispersed in sterile distilled water prior to XRD analysis, thus ruling out the presence of any free compound/protein that might independently crystallize and giving rise to Bragg reflections.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A comparison of our XRD spectrum with the standard confirmed that the silver particles formed in our experiments were in the form of nanocrystals, as evidenced by the peaks at 2 毴 values of 26.2 曘 , 27.9 曘 , and 32.3 曘 , corresponding to (125), (226), and (264), respectively, for silver. The X-ray diffraction results clearly show that the silver nanoparticles formed by the reduction of Ag + ions by the C. roseus leaf extract are crystalline in nature [26] . As mentioned in the method section, the silver nanoparticles once formed were repeatedly centrifuged and redispersed in sterile distilled water prior to XRD analysis, thus ruling out the presence of any free compound/protein that might independently crystallize and giving rise to Bragg reflections.…”
Section: Discussionmentioning
confidence: 96%
“…Its applications include jewels, utensils, currency, dental alloy, photography and explosives. Among silver's many applications, its disinfectant property is being exploited for hygienic and medicinal purposes, such as treatment of mental illness, nicotine addiction and infectious disease like syphilis and gonorrhea [26,27] . Silver nanoparticles have been demonstrated to exhibit antimicrobial properties against bacteria with close attachment of the nanoparticles themselves with the microbial cell and the activity being Theta-2Theta(dag) Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Although biosynthesis of silver nanoparticles by plants such as Desmodium triflorum [17] , Cinnamomum camphora [18] , Moringa oleifera [19] , and Eucalyptus hybrida [20] have been reported, the potential of the plants as biological materials for the synthesis of nanoparticles is currently under exploitation.…”
Section: P E E R R E V I E W Abstractmentioning
confidence: 99%
“…Mukherjee and co-workers [10] The band around 1069 cm -1 can be assigned to the ether linkages or -C-O- [14,25], whereas, the band around 1314 cm -1 and 1390 cm -1 can be assigned to geminal methyls [14] (see Fig. (5a)).…”
Section: Ftir Studiesmentioning
confidence: 99%
“…(5a)). To a large extent, the band at 1069 cm -1 might be contributed by the -C-O-groups of the polyols such as flavones, terpenoids and the polysaccharides present in the biomass [25]. The absorbance band centered at 1620 and 1653 cm -1 (5a) is associated with the stretching vibration of -C=C-or aromatic groups [14,25].…”
Section: Ftir Studiesmentioning
confidence: 99%